CHANGING TEACHERS' PRACTICES ANDPERCEPTIONS IN DEVELOPING CRITICALTHINKING AND CREATIVITY. - Choriyev Bekzod Abdirakhmonovich (Euro Asian Journal Publishing, 2026)
The article presents considerations on the development of critical thinking and creativity in the practical activities of teachers in the modern transformation of education through the use of digital technologies in education, methods of monitoring changes in teachers' perceptions, and substantiates scientific views based on industry sources
Keywords: Digital technologies; practical activities; critical thinking